Factors associated with high transmission risk and detectable plasma HIV RNA in HIV-infected MSM on ART. (September 2014) - Blumenthal, Jill; Haubrich, Richard; Jain, Sonia; Sun, Xiaoying; Dube, Michael; Daar, Eric; Milam, Joel; Morris, Sheldon
Summary: HIV transmission risk is increased during antiretroviral therapy (ART) use if individuals are not virologically suppressed and engage in high risk transmission behaviour. Baseline data of HIV-infected men who have sex with men (MSM) with recent history of risky behaviour on ART for ≥3 months ( n  = 139) were evaluated to assess predictors of detectable viraemia and HIV transmission risk-taking behaviour. Twenty-four subjects had viral load (VL) >75 copies/mL and 12 had VL >1000 copies/mL. In multivariable regression analyses, subjects with VL >75 copies/mL were more likely to be Black (OR = 4.48, p  = 0.007), have lower CD4 cell counts (OR = 0.727, p  = 0.005) and have used methamphetamines in the last month (OR = 6.64, p  = 0.019). Subjects with VL >1000 copies/mL were more likely to have lower CD4 cell counts (OR = 0.494, p  = 0.004), report <90% adherence (OR = 7.94; p  = 0.046) and have used methamphetamines in the last month (OR = 10.01, p  = 0.034). Subjects with VL >75 copies/mL with the greatest transmission risk behaviour ( n  = 14) were more likely to be Black (OR = 8.00, p  = 0.006), have lower CD4 cell counts (OR = 0.657, p  = 0.009) and have used methamphetamines in the last month (OR = 5.20, p  = 0.042). High risk HIV transmission behaviour with viraemia occurred in 10% of the cohort. Future efforts to reduce HIV transmission among MSM on ART will require combined interventions that target risk-taking behaviours and substance use.